Incidence and Characteristics of Skin Cancer Patients at Dr. Mohammad Hoesin General Hospital, Palembang - Hardianto, Alvendro; Qodir, Nur; Roflin, Eddy; Indra, Bima (http://dharmais.co.id/, 2025)
Background: Breast-related new skin cancer cases have increased annually over the past decade. Current data on new skin cancer cases is essential as a preliminary step in preventing and reducing the incidence of new cases. This study aims to determine the incidence and characteristics of skin cancer patients at Dr. Mohammad Hoesin General Hospital, Palembang, from 2019 to 2021.Methods: This observational descriptive study employed a cross-sectional design using total sampling. Data were obtained from the medical records of skin cancer patients at Dr. Mohammad Hoesin General Hospital between January 2019 and December 2021. The variables analyzed included demographic characteristics (age, gender, occupation, education, marital status, and residence), cancer type, cancer stage, and tumor location. The data were analyzed using descriptive statistics to determine the frequency and distribution of each variable. Results: The incidence and characteristics of skin cancer at Dr. Mohammad Hoesin General Hospital were recorded in 38 patients. Basal cell carcinoma was the most common type, accounting for 44.74% of cases. Most patients were aged 45-64 years (52.6%), unemployed or housewives (65.8%), female (65.8%), had completed high school (44.7%), were married (89.5%), and resided outside Palembang (55.3%). Most cases were diagnosed at stage I (44.7%) and were primarily located in the head and neck region (76.3%). Early-stage diagnosis is associated with better survival rates, while advanced-stage cancers, are more aggressive and require prompt treatment for improved survival outcomes. Understanding these factors is crucial for optimizing patient management and resource allocation.Conclusions: The study shows basal cell carcinoma as the most common skin cancer at Dr. Mohammad Hoesin General Hospital, with a higher incidence in females, especially those aged 45–64, unemployed or housewives, married, and living outside Palembang. Most cases were diagnosed early and located in the head and neck